Blindness - O ensaio sobre cegueira de Fernando Meirelles: a visão do realizador - Silva, Fabiane Pimentel (2014)
In 2008 the director Fernando Meirelles presented to the public the movie Blindness (Blindness), which has the title of Blindness in Brazil, it was a very desired achievement by Brazilian filmmaker. To make the film, Meirelles received the script ready producer Niv Fichman Canadian after being invited in 2006 to perform a version for the screen. The filmmaker considered the invitation to direct the film, plus a surprise, "frightening coincidence" because he had tried to buy the rights to the novel a few years before in an attempt to film the story, but the Portuguese refused to author such proposal. This time after insistence Fichman, Saramago authorizing the filming of the novel and follows the development of the work of Meirelles. The movie script was adapted by Don McKellar, and is an independent co-production Canada, Brazil, Japan. Besides the script, the director used the text of the novel to work with the actors on stage, proposing that everyone read the book including the crew. In the film, Meirelles also bothered to consider the iconographic relations linked to the visual metaphors so characteristic of the text Saramago, and maintained in the audiovisual. The objective of the research focused on the process of creation and direction of the film from the vision of the director.